2000
DOI: 10.1021/jp993734a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reactions of Living Polymers:  Density Functional Study of Reactivity of Phenol and Phenoxides with the Cyclic Tetramer of Polycarbonate

Abstract: The reactivity of phenol, lithium phenoxide (LiOPh), and sodium phenoxide (NaOPh) with the cyclic tetramer of bisphenol A polycarbonate (BPA-PC) has been investigated using density functional calculations. The potential energy of the system is computed using a suitable reaction coordinate and relaxing all other degrees of freedom by Car-Parrinello molecular dynamics. Both LiOPh and NaOPh catalyze ring opening with small energy barriers (∆E ) 4.0, 2.5 kcal/mol, respectively) to a chain with a phenyl carbonate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
1
22
1
Order By: Relevance
“…I. 9 An attack involving the (positively charged) metal atom is most likely at the carbonate group, as confirmed by experimental studies on a number of functionalized bisphenols using a variety of catalysts. 10 Therefore, we have performed a constrained simulation using the distance Rc between the carbonyl C and the reactant Ο as the initial reaction coordinate.…”
Section: Reactions Of Phenoxides With Cyclic Tetramermentioning
confidence: 88%
See 1 more Smart Citation
“…I. 9 An attack involving the (positively charged) metal atom is most likely at the carbonate group, as confirmed by experimental studies on a number of functionalized bisphenols using a variety of catalysts. 10 Therefore, we have performed a constrained simulation using the distance Rc between the carbonyl C and the reactant Ο as the initial reaction coordinate.…”
Section: Reactions Of Phenoxides With Cyclic Tetramermentioning
confidence: 88%
“…shows six snapshots of the trajectory for the reaction of LiOPh ap proaching from outside the cyclic tetramer 9. The reactants interact weakly for Rc ~ 4, with steric hindrances from neighboring phenyl rings giving rise to an energy barrier of 4 kcal/mol at Rc = 3.8 Â.…”
mentioning
confidence: 99%
“…The latter can be used for the photometric detection of phenol as in the case of diazotized 4-nitroaniline. Salicylic acid (2-hydroxybenzoic acid) can be produced by the Kolbe-Schmitt reaction 26 (studied by the density functional method 27 ) from sodium phenolate and carbon dioxide, whereas potassium phenolate gives the para compound. Alkylation and acylation of phenol can be carried out with aluminium chloride as catalyst; methyl groups can also be introduced by the Mannich reaction.…”
Section: A Summary Of Key Physico-chemical Properties Of Phenolmentioning
confidence: 99%
“…Adapted from Reference 220 with permission to Subsection III.A, we can estimate its energy of formation as the energy difference between the cis ortho-and trans ortho-CPs which, at the present computational level, is 10.0 kJ mol −1 after including ZPVE corrections. It is worthwhile to deduce the order of stability of cyanophenols similar to that given in equation 12 (27) It shows that, energetically, all cyanophenols fall into the interval of stability between the cis ortho-and trans ortho-CPs. Some characteristic vibrational modes are collected in Table 25 accompanied by their assignments based on the PEDs.…”
Section: Some Representatives Of Substituted Phenolsmentioning
confidence: 99%
“…The carboxylic branching structure observed in reactive pyrolysis in MM-PC production 3 indicated that the PC chain is most susceptible to branching at the carbonate group, where transesterification occurs in PC synthesis. [4][5][6] In some cases branching is desired, because longchain branched PC modifications show special shear viscosity behavior that makes them suitable for blow molding applications. The degree of branching can be controlled by branching agents such as THPE [1,1,1-tris(p-hydroxyphenol)ethane] 7 and polyphenols.…”
Section: Introductionmentioning
confidence: 99%